2019
DOI: 10.1103/physrevb.100.224519
|View full text |Cite
|
Sign up to set email alerts
|

Long-ranged triplet supercurrent in a single in-plane ferromagnet with spin-orbit coupled contacts to superconductors

Abstract: By converting conventional spin-singlet Cooper pairs to polarized spin-triplet pairs, it is possible to sustain long-ranged spin-polarized supercurrents flowing through strongly polarized ferromagnets. Obtaining such a conversion via spin-orbit interactions, rather than magnetic inhomogeneities, has recently been explored in the literature. A challenging aspect with regard to experimental detection has been that in order for Rashba spinorbit interactions, present e.g. at interfaces due to inversion symmetry br… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…The described mechanism has the same physical origin as the one reported in Ref. [98], where the gradients of pairing amplitude arising near the edges of S and Pt layers in the planar geometry in combination with Rashba SOC can generate LRTs. In our proposal LRTs are generated within the entire Pt layers thus providing much larger long-range Josephson currents.…”
supporting
confidence: 64%
See 2 more Smart Citations
“…The described mechanism has the same physical origin as the one reported in Ref. [98], where the gradients of pairing amplitude arising near the edges of S and Pt layers in the planar geometry in combination with Rashba SOC can generate LRTs. In our proposal LRTs are generated within the entire Pt layers thus providing much larger long-range Josephson currents.…”
supporting
confidence: 64%
“…For the superconducting gap in Nb ∼ 10 K so that the critical current is I c ∼ 10 −1 (p s ξ ) 2α2 A. Takingα ∼ 0.1-1 [27,89,112] and p s ξ = 0.3, we get the current I c ∼ 10 −2 -10 −4 A which is much larger than in SFS junctions where LRTs are generated by the magnetic inhomogeneity [49]. This I c is much larger than obtained for the planar geometry [98] because in our mechanism there are no physical limitations on the junction cross section.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Another theoretical and subsequent experimental work demonstrated that the superconducting condensation energy can induce the magnetic reorientation in a ISOC-present SC/FM heterostructure. 75,76 We also note that vertical heterostructures with in-plane magnetization and ISOC interaction have been experimentally explored, but LRTC due to ISOC have not been observed. 77,78 Based on previous theoretical works, 73 the conditions for the generation of LRTC by SOC are quite restrictive in vertical structures, more favourable layouts are involving lateral structures where supercurrents have a component flowing in the direction parallel to the hybrid interfaces.…”
Section: Figmentioning
confidence: 94%
“…[21][22][23][24][25][26][27][28][29][30][31][32][33][34] Signatures of long-range proximity have also been reported for ferromagnetic Josephson junctions containing a heavy metal. [35][36][37][38][39][40][41] In parallel, a substantial body of theoretical studies have considered the possibility of generating and controlling LRT correlations using spin-textured systems, such as domain walls [42][43][44][45][46] and vortices. 47,48 However, the experimental evidence to verify such models remains scarce.…”
Section: Introductionmentioning
confidence: 99%